2005
DOI: 10.1055/s-2004-813905
|View full text |Cite
|
Sign up to set email alerts
|

Kosteneffektivität von Screening auf Amblyopie

Abstract: Screening for amblyopia meets the basic requirements of cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…The main limitation of the early Konig and Barry papers, 159,162,163 and the other German studies, 166,167 is that they do not facilitate the evaluation of screening programmes based at alternative ages. Moreover, they do not describe the effects of identifying the target conditions for the screening programmes.…”
Section: Discussion Of Economic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main limitation of the early Konig and Barry papers, 159,162,163 and the other German studies, 166,167 is that they do not facilitate the evaluation of screening programmes based at alternative ages. Moreover, they do not describe the effects of identifying the target conditions for the screening programmes.…”
Section: Discussion Of Economic Studiesmentioning
confidence: 99%
“…Of 11 identified economic papers, seven were published by the same German research team, seemingly led by Konig and Barry. [159][160][161][162][163][164][165] Two other separate German studies were identified, 166,167 and also two US-based studies.…”
Section: Review Of Previous Economic Analyses Of Screening For Amblyopiamentioning
confidence: 99%
See 1 more Smart Citation
“…48 • Concerns about bullying of children, especially with eye patching, at school leading to poor compliance 51 further support earlier treatment of amblyopia, i.e., prior to school entry. 52 The Screening Program • Screening for amblyopia is cost-effective; 53 universal eye examination for preschool children has a low cost per QALY. 8 • The location of the screening program is likely to affect uptake.…”
Section: The Treatmentmentioning
confidence: 99%
“…Die Behandlung der Amblyopie mit Okklusion stellt seit Jahrzehnten eine etablierte Methode dar. Der Nutzen der Okklusionsbehandlung liegt vor allem in der Vermeidung von Kosten, die entstehen, wenn Patienten mit unzureichend behandelter Amblyopie im Laufe des Lebens ihr gutes Auge verlieren [15]. Der Zeitraum, den ein solcher Patient beidseitig sehbehindert (Visus beidseits > 0,3 logMAR) verbringt, verlängert sich etwa von 8 auf 15 1 / 2 Monate [9].…”
unclassified